Brief Report: Association of CCR1, KLRC4, IL12A–AS1, STAT4, and ERAP1 With Behçet's Disease in Iranians. Issue 10 (23rd September 2015) - Sousa, Inês; Shahram, Farhad; Francisco, David; Davatchi, Fereydoun; Abdollahi, Bahar Sadeghi; Ghaderibarmi, Fahmida; Nadji, Abdolhadi; Mojarad Shafiee, Niloofar; Xavier, Joana M.; Oliveira, Sofia A.
Abstract : Objective: To independently replicate the top findings from 4 published genome‐wide association studies (GWAS) of susceptibility genes in Behçet's disease (BD). Methods: We tested 14 single‐nucleotide polymorphisms (SNPs) in 13 genomic loci (excluding the major histocompatibility complex [MHC], IL10, and IL23R–IL12RB2, which have already been associated with BD in Iranians) for allelic and genotypic associations with BD in 973 patients and 828 controls from Iran and performed meta‐analyses of the significantly associated markers. Results: Six SNPs (in decreasing order of significance, rs7616215 located 38 kb downstream of CCR1, rs2617170 [p.Asn104Ser] in KLRC4, rs17810546 in IL12A–AS1, rs7574070 in STAT4, and rs10050860 [p.Asp575Asn] and rs13154629 in ERAP1 ) were nominally associated with BD in both allelic association tests (5.05 × 10 −9 ≤ P allele ≤ 7.55 × 10 −3 ) and sex‐adjusted genotypic association tests (6.01 × 10 −9 ≤ adjusted P value ≤ 1.30 × 10 −2 ). For all 6 SNPs tested by meta‐analysis ( P meta ), the association with BD was strengthened, because the direction and magnitude of association were similar across populations (e.g., for rs7574070, odds ratio [OR] for A allele 1.29 [95% confidence interval (95% CI) 1.21–1.37], P meta  = 2.34 × 10 −16 ; for rs7616215, OR for C allele 0.70 [95% CI 0.65–0.76], P meta  = 1.54 × 10 −19 ; for rs17810546, OR for A allele 0.60 [95% CI 0.52–0.70], P meta  = 6.34 × 10 −11 ; for rs2617170, OR for T allele 0.76 [95% CI 0.70–0.81], P meta  = 2.75 × 10 −14 ; for rs13154629, OR for TT genotype 2.76 [95% CI 2.01–3.80], P meta  = 3.57 × 10 −10 ). Conclusion: This study reinforces the notion that CCR1, KLRC4, IL12A–AS1, STAT4, and ERAP1 are bona fide susceptibility genes for BD, in addition to the MHC, IL10, and IL23R–IL12RB2 loci. Future genetic and functional studies are now warranted to uncover the roles of these genes in the pathogenesis of BD.